2008
DOI: 10.1128/cvi.00219-08
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity between Immunoglobulin G Antibodies of Whales and Dolphins Correlates with Evolutionary Distance

Abstract: Growing morphological and molecular evidence indicates that the porpoises, dolphins, and whales evolved within the even-toed ungulates, formerly known as Artiodactyla. These animals are now grouped in the Cetartiodactyla. We evaluated the antigenic similarity of the immunoglobulin G (IgG) molecules of 15 cetacean species and the domestic cow. The similarity was scored using three distinct antibodies raised against bottlenose dolphin (Tursiops truncatus) IgG in a Western blot, an indirect enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
(37 reference statements)
1
14
1
Order By: Relevance
“…As shown here and by others (38), in odontocetes, the cross-reactivity of immunoglobulins is extensive, thereby allowing the use of a single species anti-IgG antibody for discriminating the presence of anti-Brucella LPS antibodies. The fact that kappa values of the iELISA were considerably higher than those of the gELISA and cELISA regardless of whether the serum sample tested belonged to the homologous species (S. bredanensis) or to the heterologous species (Kogia spp.)…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown here and by others (38), in odontocetes, the cross-reactivity of immunoglobulins is extensive, thereby allowing the use of a single species anti-IgG antibody for discriminating the presence of anti-Brucella LPS antibodies. The fact that kappa values of the iELISA were considerably higher than those of the gELISA and cELISA regardless of whether the serum sample tested belonged to the homologous species (S. bredanensis) or to the heterologous species (Kogia spp.)…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, all these families are phylogenetically closer to the family Delphinidae, of which S. bredanensis is a member (37). Regarding the very low cross-reactivity between odontocete immunoglobulins and gray whale (Eschrichtius robustus) and humpback whale (Megaptera novaeangliae) antibodies (38), it is unlikely that this same anti-dolphin IgG would work for Mysticeti (baleen whales), an order that belongs to a different phylogenetic branch among cetaceans (37). Finally, based on limited experience with commercial anti-dolphin IgG(HϩL) antibodies, we predict that extensive cross-reactions with odontocete sera will be observed with these reagents.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of unknown closely related organisms that may cross-react is a possibility as observed in cetacean species (Nollens et al 2008). There is antigenic similarity between T. gondii and Hammondia hammondi (Riahi et al 1998), as well as between T. gondii and Neospora caninum (Zhang et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…17 For whales, it has been shown that Abs against IgG of toothed whales had a reduced ability to recognize IgG of baleen whales, 28 demonstrating the rationale of producing species-particular Abs against each host species of interest. This often has the drawback of necessitating the production of a finite amount of antispecies Abs in experimental animals that has to be renewed, which is not in line with the principles of reduction, refinement, and replacement of animal testing.…”
Section: Discussionmentioning
confidence: 99%